Differences in the Effectiveness of Moringa Seed Powder (Moringa oleifera) and Tamarind (Tamarindus indica) in Reducing Chemical Oxygen Demand (COD) Levels - Sri Abel W Tahir; Herlina Jusuf; Ayu Rofia Nurfadillah (Universitas Muhammadiyah Palu, 2026)
Industrial tofu liquid waste is waste produced from the tofu production process, such as soy washing and boiling, which has the characteristics of brownish-yellow, pungent stench and contains high organic matter. Tofu industrial liquid waste contains Chemical Oxygen Demand (COD) levels. The purpose of the study was to analyze the difference between moringa seed powder, tamarind seed powder and the combination of the two on the decrease in Chemical Oxygen Demand (COD) levels in tofu industrial liquid waste. The type of laboratory experiment research with a Complete Random Design (RAL) research design uses moringa seed powder, tamarind and a combination of the two with a dose variation of 3 grams, 4 grams and 5 grams. The sample is 6 liters of tofu wastewater obtained using the grab sample technique. The test used was Kruskal-Waliis The initial COD level in this study was 1800 mg/L The results of this study showed that the initial COD level in tofu liquid waste was 1800 mg/L. The effectiveness of coagulants in reducing COD levels was 5 grams of moringa powder, 5 grams of tamarind and a combination of 5 grams with a percentage reduction of 85%, 89% and 90% respectively. There was no difference in decrease in each dose used to lower COD levels (p-value = 0.368). It is recommended to test other variables such as sedimentation time, as well as stirring variations.